Results of the Nellix system investigational device exemption pivotal trial for endovascular aneurysm sealing - Carpenter, Jeffrey P.; Böckler, Dittmar (Journal of vascular surgery, 2016)
Objective The Nellix EndoVascular Aneurysm Sealing system (Endologix, Inc, Irvine, Calif) is a novel approach to abdominal aortic aneurysm (AAA) endovascular repair whereby biocompatible polymer is employed to exclude and to seal the AAA sac. We report 30-day results of the U.S. pivotal trial. Methods Consecutive, eligible, consenting patients were enrolled at 29 sites in the United States and Europe. Inclusion criteria required an asymptomatic infrarenal AAA, with aortic neck length ≥10 mm and angle to the sac ≤60 degrees, aortic neck diameter of 18 to 32 mm, aneurysm blood lumen diameter ≤6 cm, common iliac artery lumen diameter of 9 to 35 mm, access artery diameter ≥6 mm, and serum creatinine level ≤2 mg/dL. Follow-up at 30 days included clinical assessment and computed tomography angiography evaluation of endoleaks and device integrity as assessed by a core laboratory. The primary safety end point is the incidence of independently adjudicated 30-day major adverse events (MAEs), with success defined as superiority with reference to the Society for Vascular Surgery open repair control group (56%). Results Between January and November 2014, 150 trial patients having a mean AAA diameter of 5.8 cm were enrolled and treated with the Nellix system with 100% procedural success. One early death (0.7%) occurred secondary to multisystem organ failure. All 149 surviving patients completed 30-day follow-up. There were no aneurysm ruptures, conversions, limb thromboses, stent fractures, or stent kinking. Five early MAEs occurred in four patients (2.7%) and included one death, bowel ischemia (1), renal failure (2), and respiratory failure (1). One (0.7%) secondary intervention to treat inadvertent coverage of a renal artery was performed. The core laboratory identified nine (6%) endoleaks (one type I, eight type II) on 30-day computed tomography angiography. Freedom from MAE was 97.3% (95% confidence interval, 93.3%-99.0%). Conclusions In selected patients, perioperative outcomes with the Nellix system for endovascular aneurysm sealing are encouraging, with very low 30-day morbidity and mortality and high procedural success. The primary safety end point has been achieved. Longer term follow-up is in progress.